Versatile electroanalysis of cellular receptor: The case of Toll-like immune receptors evaluated on transfected human cell - Mendonça-Natividade, Flávia Costa; Carvalho, Fernanda C. [UNESP]; Roque-Barreira, Maria-Cristina; Bueno, Paulo R. [UNESP] (Elsevier, 2017)
In the present work we compare the results obtained by two approaches to detect receptor expression on cells surface: (i) the confocal laser scanning microscopy, which is an established methodology to study cell biology and associated events, wherein the cells or molecules labeling is needed, and (ii) an alternative label-free electroanalytical technique, essentially quantitative, based on Electrochemical Impedance Spectroscopy (EIS). Concerning specificity, both assays are equivalent, since they depend on the antibody efficiency to recognize and discriminate the searched structure in the cell context. Regarding sensitivity, we showed that, in the case of the detection of Toll-like receptor on transfected human cells, this label-free EIS approach (with measurements performed on 2% of paraformaldehyde, an environment that retained morphology and antigenic sites of cells), was very sensitive for the receptor detection, in a demonstration that the proposed electrical impedance analytical assays can help optimizing the ability to evaluate cellular biological events. It provides to biologists and medical community an alternative and either quantitive analytical tool that can be applied to the biological model of interest and used to design and perform a rapid multiplexable and automatable assaying methodology.
Keywords: Biological assay; Cell biology; Electrochemical impedance spectroscopy (EIS); Toll-like receptor